2020
DOI: 10.3390/app10165491
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Magnesium Ion Concentration on the Scale Inhibition of Heat Exchanger in Circulating Cooling Water under Alternating Electric Field

Abstract: This work investigated the effect of magnesium ion concentration on the formation of mineral scale in circulating cooling water under alternating electric field treatment (AEFT) by using a self-made power plant circulating cooling water simulator. In this experiment, the circulating cooling water used was artificial hard water. Three experimental groups with different magnesium ion concentrations and three corresponding control groups were studied. Scale inhibition rate, fouling resistance, calcium ion concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…However, when the concentration of magnesium chloride reaches 4mmol/L, the electromagnetic field has a significant promoting effect on the growth of attached scale. When the concentration was increased to 6mmol/L, the electromagnetic field could significantly inhibit the growth of attached scale [37]. Y [38] also studied the effects of different concentrations of Cu 2+ , Fe 2+ , and Fe 3+ on the microstructure and crystal structure of CaCO 3 fouling.…”
Section: Water Quality Parametersmentioning
confidence: 99%
“…However, when the concentration of magnesium chloride reaches 4mmol/L, the electromagnetic field has a significant promoting effect on the growth of attached scale. When the concentration was increased to 6mmol/L, the electromagnetic field could significantly inhibit the growth of attached scale [37]. Y [38] also studied the effects of different concentrations of Cu 2+ , Fe 2+ , and Fe 3+ on the microstructure and crystal structure of CaCO 3 fouling.…”
Section: Water Quality Parametersmentioning
confidence: 99%
“…In this study, under the two high hardness water conditions investigated, the combined scale inhibition effect of the electrostatic field and Mg 2þ is weakened and even promotes scaling. Zhang et al (2020) studied the effect of alternating electric field and Mg 2þ on CaCO 3 scaling, indicated that Mg 2þ concentrations of 6 mmol/L have a potential scale inhibition effect after treatment in the HVAC electric field. Under the two different water conditions in this study, the HVAC electric field treatment also showed favorable scale inhibition effects.…”
Section: Sem and Xrd Analysismentioning
confidence: 99%
“…Additionally, impurity ions such as carbonate (HCO 3 − ), phosphate (PO 4 3− ), and nitrate (NO 3 − ) enter the CCW along with rainwater or suspended particles in the air, causing an increase in hardness and alkalinity [11]. As the hardness and alkalinity ions encounter heat exchanger surfaces during the circulation of cooling water, precipitation quickly occurs due to the higher temperatures, ultimately leading to scaling on the surfaces of heat exchangers and pipes [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%